Accelerating Change of Practice Through Targeted Professional Development in Data Science - Kursav, Merve N.; Pauls, Scott D.; Bonfert-Taylor, Petra; Loeb, Lorie; Ray, Laura (Journal of statistics and data science education, 2025)
DIFUSE is a National Science Foundation-funded project at Dartmouth College that develops flexible and reusable data science modules. To disseminate our work, we organized a workshop where faculty participants explored modules and the design process. We identify factors that led participants to join the workshop, their goals for incorporating data science in their courses, and their impacts on their practice. We report and interpret quantitative and qualitative outcomes through participants’ surveys and interviews, finding that the workshop was very successful in increasing participants’ resources and experience levels and promoting change of practices. Further, participants who engaged in continued collaboration, adapting or creating modules for their own courses, reaped deeper changes in practice.